2011
DOI: 10.1007/s00244-011-9655-1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Chlorpyrifos to Larval Rana dalmatina: Acute and Chronic Effects on Survival, Development, Growth and Gill Apparatus

Abstract: Chlorpyrifos [O,O-diethyl-O-(3,5,6-trichloro-2-pyridyl)phosphorothioate] is a widely used non-systemic organophosphorus insecticide frequently detected in surface waters around the world. The goal of this study is to evaluate the acute and chronic effects of this insecticide on Rana dalmatina tadpoles. To assess the sensitivity of this species, the LC50 value (i.e. the concentration at which 50% of tadpoles die) was determined after 96 h. Our results showed that 5.174 mg L(-1) chlorpyrifos caused 50% mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 60 publications
1
38
0
3
Order By: Relevance
“…Connection to teratogenesis by growth inhibition in larvae remained unclear, although total length decrease in larvae occurred at concentrations more than five times lower than the LC 50 value. Bantle et al 1999;Fort and Rogers 2005) Narcotic effects are usually observed during exposure of early developmental stages of anurans to insecticides (e.g., Bernabò et al 2011;Yu et al 2013). For example, twitching, convulsion, and narcosis in X. laevis embryos was observed during exposure to a-cypermethrin (Yu et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Connection to teratogenesis by growth inhibition in larvae remained unclear, although total length decrease in larvae occurred at concentrations more than five times lower than the LC 50 value. Bantle et al 1999;Fort and Rogers 2005) Narcotic effects are usually observed during exposure of early developmental stages of anurans to insecticides (e.g., Bernabò et al 2011;Yu et al 2013). For example, twitching, convulsion, and narcosis in X. laevis embryos was observed during exposure to a-cypermethrin (Yu et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…affect development at the biochemical and endocrine levels with maladaptive ramifications for behavior, growth, and longevity in amphibians and fish (Bernabo et al 2011;Weis et al 2001). Early exposure to food limitation or disrupted parental care in birds and mammals, or low socioeconomic status in humans, affects neural development related to cognition (Buchanan et al 2013).…”
mentioning
confidence: 99%
“…This insecticide poisons the stomach of the pest (Kienle et al, 2009) and inhibits enzyme activity by binding the enzyme acetyl cholinesterase (AChE) through phosphorylation (Palma et al, 2009;Jin et al, 2015). Its' potential danger to humans, however, has made the US Environmental Protection Agency impose a ban on its sale for residential use (US EPA, 2006), while no such ban exists in Europe as chlorpyrifos is one of the top-selling insecticides (Bernabò et al, 2011). Chlorpyrifos is relatively persistent in nature as compared to other organophosporus insecticides, with a half-life in watersediment systems ranging from 29 to 74 days (Palma et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorpyrifos shows a high toxicity to non-target aquatic organisms including vertebrates (Kienle et al, 2009;Bernabò et al, 2011;Xing et al, 2012;Jin et al, 2015) and invertebrates (Daam et al, 2008;Palma et al, 2009;Rubach et al, 2011Rubach et al, , 2012. Like other groups of vertebrates, fish embryos and larvae are also considered to be the most sensitive stages in the life cycle and sensitive to low levels of environmental pollutants (Marimuthu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation